Social Security Protection for Laid-Off Workers in the Sritex Mass Retrenchment: A Welfare State Analysis - Dewi Ningrum Purbasari; Raihan Nafis Abrar; Muhammad Fauzi Rais (Universitas Negeri Semarang, 2026)
This study examines whether Indonesia's Job Loss Insurance (JKP) and Old Age Security (JHT) programs have fulfilled the state's obligation to protect workers affected by mass layoffs from corporate bankruptcy, using the Sritex case as the primary reference. This study employs a normative juridical approach analyzing relevant legislation against the ICESCR, General Comment No. 19, and ILO Convention No. 102. The findings reveal four structural gaps: an eligibility gap, an adequacy gap, a legal uncertainty gap in JHT, and an insolvency gap due to the absence of a wage guarantee fund. These gaps demonstrate that Indonesia's social security framework remains insufficient to fulfill its constitutional and international obligations in cases of large-scale mass layoffs. Structural reform is needed to strengthen the state's role as the primary guarantor of workers' social rights.